Carnavalização e antropofagia no metacinema de Carlos Reichenbach - Pereira, Carlos Eduardo (2013)
This research analyses carnavalization and antropophagy in Carlos Reichenbach`s filmography from the late 1960s until 1983, produced at Boca do Lixo, São Paulo. The work also studies meta-language, anti-illusionism and hipertextuality as the main characteristics of this unique and outstanding body of work in Brazilian cinema. The dissertation structures specific conceptual and theoretical fields in order to investigate Reichenbach s eleven features including three in episodes. The main authors used as reference here were Roberto DaMatta, Mikhail Bakhtin, Oswald de Andrade, Gérard Genette, Robert Stam, Margaret A. Rose, Tzvetan Todorov, Jairo Ferreira, and Carlos Reichenbach himself. Through the use of a revised bibliography, critical material, related documentation such as press-releases, interviews, visual materials such as film stills and publicity, mostly found at both Cinemateca do MAM and Cinemateca Brasileira documentation centers, and through close analyses of the films paratexts, the dissertation aims at revising the critical fortune surrounding Carlos Reichenbach, therefore shedding new light and hypothesis on the work of this influential filmmaker